High-Fat Diet Alters Immunogenic Properties of Circulating and Adipose Tissue-Associated Myeloid-Derived CD45+DDR2+ Cells - Sara J. Sidles; Ying Xiong; M. Rita I. Young; Amanda C. LaRue (Mediators of Inflammation)
Chronic inflammation is evident in the adipose tissue and periphery of patients with obesity, as well as mouse models of obesity. T cell subsets in obese adipose tissue are skewed towards Th1- and Th17-associated phenotypes and their secreted cytokines contribute to obesity-associated inflammation. Our lab recently identified a novel, myeloid-derived CD45+DDR2+ cell subset that modulates T cell activity. The current study sought to determine how these myeloid-derived CD45+DDR2+ cells are altered in the adipose tissue and peripheral blood of preobese mice and how this population modulates T cell activity. C57BL/6 mice were fed with a diet high in milkfat (60%·kcal, HFD) ad libitum until a 20% increase in total body weight was reached, and myeloid-derived CD45+DDR2+ cells and CD4+ T cells in visceral adipose tissue (VAT), mammary gland-associated adipose tissue (MGAT), and peripheral blood (PB) were phenotypically analyzed. Also analyzed was whether mediators from MGAT-primed myeloid-derived CD45+DDR2+ cells stimulate normal CD4+ T cell cytokine production. A higher percentage of myeloid-derived CD45+DDR2+ cells expressed the activation markers MHC II and CD80 in both VAT and MGAT of preobese mice. CD4+ T cells were preferentially skewed towards Th1- and Th17-associated phenotypes in the adipose tissue and periphery of preobese mice. In vitro, MGAT from HFD-fed mice triggered myeloid-derived CD45+DDR2+ cells to induce CD4+ T cell IFN-γ and TNF-α production. Taken together, this study shows that myeloid-derived CD45+DDR2+ cells express markers of immune activation and suggests that they play an immune modulatory role in the adipose tissue of preobese mice.